Catamenia and endometrial changes in users of combined oral contraceptives - Siu Au, Alejandro (2015)
We prospectively studied 237 users of combined oral contraceptives, evaluating changes in catamenia and endometrial histological findings. progressive decline of the rule which in some cases to amenorrhea, and spotting was found in the first cycles of treatment. In the histological study of the endometrium it was taken as parameter changes in the glandular epithelium, stroma and vessels. The epithelium was a large percentage of glandular atrophy. In the stroma he predominated predecidual metaplasia and edema; Total found no fibrosis, and vascular changes predominant vascular dilation and less prominence. The decline of the menstrual flow is directly related to the findings described; also produced endometrial atrophy is completely reversible, since no fibrous lesion, but this is due to the reduction of glandular and stromal components. No photo found premalignancy or neoplastic lesions.